METODE REWARD-PUNISHMENT KONSEP PSIKOLOGI DAN RELEVANSINYA DENGAN ISLAM PERSPEKTIF HADIS - Harpan Reski Mulia (UIN Sunan Kalijaga Yogyakarta, 2017)
In many methods that can be used to make better education, one of them is by using methods of reward and punishment or reward and punishment. The use of this method is based on, that people love to get reward and do not like to get punishment. These basics are meant in the context of Islam in order to express about Islam in methods of reward and punishment. Not just Muslim translations, much more is learned in the context of hadith. After tracing in the context of Islam it was found out that Islamic Educational figures believed in such methods, such as Ibn Sina, al-Gazali and Abdullah Nasih Ulwah, although with a note using a better method of punishment, in educating children, then giving also not and will be easily, and the punch can be done with a punch that does not involve children. In the concept of hadith also found from the search results of the Apostle's Apostle, and did the same. Based on research on sanad and matan hadith, which is related to reward and punishment, it is found that it is legitimate and well-known hadiths also known as gifts, the punishment addressed in the method of reward and punishment in this paper is authentic hadith accepted. Keywords: reward, punishment, concept of psychology, concept of Islam, study of hadis.